2011
DOI: 10.3892/etm.2011.314
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Acer mono Max. sap on water immersion restraint stress-induced gastric ulceration

Abstract: Abstract. Acer mono Max. sap (AmMs) is called 'Gol-Li-Su' or 'Go-Lo-Soe' in Korean, which means 'water beneficial to the bones'. It is reported that the sap contains several types of minerals and sugars. In particular, the calcium concentration of the sap is 36.5 times higher than that of commercial mineral water. Apart from its anti-osteoporosis effect, no reports have addressed the biological activities of AmMs against degenerative diseases. In the present study, we investigated whether AmMs alleviates gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We found that NO may have protective effects against stress induced ulcer. In support of our results, some studies have shown the role of endogenous NO in the protection of gastric mucosa in stress ulcer models [45,46].…”
Section: Discussionsupporting
confidence: 91%
“…We found that NO may have protective effects against stress induced ulcer. In support of our results, some studies have shown the role of endogenous NO in the protection of gastric mucosa in stress ulcer models [45,46].…”
Section: Discussionsupporting
confidence: 91%
“…Researchers have developed many in vivo gastric ulcer models with different gastropathic mechanisms. 6 Among them, the ethanol-, indomethacin-, and water immersion restraint stress (WIRS)-induced models have been used in many studies to screen antiulcer substances, 7 , 8 , 9 because alcohol, nonsteroidal anti-inflammatory drugs, and stress are major risk factors in human life for peptic ulcers and other gastrointestinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Data are presented as means ± standard deviation (SD). The statistical values were analysed using an ANOVA with the Tukey post hoc test (Park, Son 2011 ). p Values <0.05 were set as statistically significant.…”
Section: Methodsmentioning
confidence: 99%